Eco-Moms and Climate Change: The Moderating Effects of Fertility in Explaining Gender Differences in Concern. (October 2019) - Price, Carmel E.; Bohon, Stephanie A.
Women typically report greater concern for the environment, including climate change, than men. The eco-mom theory—the belief that women have greater environmental concern than men because mothers primarily care about the health and safety of their children, while fathers primarily care about the economic support of their household—is often proffered as an explanation for this difference. Researchers who have previously tested the eco-mom theory have narrowly operationalized parenthood; we are skeptical of this theory and believe it needs additional testing. We look at fertility in relation to concern for climate change using the 2010 General Social Survey. Modeling parenthood like previous studies, we find no differences in concern for climate change between women who have children and those who do not. Modeling fertility, we find that having more children is associated with less concern for climate change for women but not men. Additionally, we find no gender difference in concern for climate change for those with many children, but these findings are complicated by education. Overall, we refute the eco-mom theory and call for new climate change survey data that better capture gender roles and identity as well as more qualitative inquiries into public concern for climate change.